Pengaruh Tingkat Suku Bunga Bank Indonesia, Jumlah Uang Beredar dan Tingkat Inflasi Terhadap Indeks Harga Saham Gabungan di Indonesia - Aditya; Arafat, Fauzi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
A country's capital market is an important part of its economic structure and a major force behind its economic dynamics. An indicator of the overall performance of the Indonesian capital market is the Jakarta Composite Index (JCI). The purpose of this study is to examine how the Jakarta Composite Index (JCI) is affected by the Bank Indonesia interest rate (BI-Rate), money supply (JUB), and inflation rate. Multiple linear regression analysis was used to examine secondary data from January 2021 to December 2023. The results show that while BI-Rate and JUB have a large negative influence on JCI, inflation has a large positive influence. These factors accounted for 83.7% of the variance in JCI, based on the Adjusted R Square value of 0.837. With a significance level of less than 0.001 and an F value of 60.899, the regression model is statistically significant. For investors and policy makers, this study provides important insights into how macroeconomic issues impact the dynamics of the JCI.